"SynMax": A mathematics application tool for Down syndrome children - Shafie, A. (2013)
Research has shown that the number skills delayed relative to reading skills for Down Syndrome (DS) children. The DS children use the same learning strategy as the normal children, but their learning stages develop more slowly. A possible solution using computer based application, which the children can interact with material that have the integration of visual information and auditory. This paper describes the design, implementation and evaluation of a computer application for learning basic numeracy skills for DS. This application consists of three modules; learning identifying numbers, matching and counting. Dual Coding theory, Schema learning theory and Rapid Application Development (RAD) is employed in the design. Initial user acceptance test of the prototype has shown positive results. Â© 2013 Springer International Publishing.